Broadening Intellectual Diversity in Visualization Research Papers - Lee, Bongshin; Isaacs, Kate; Szafir, Danielle Albers; Marai, G. E.; Turkay, Cagatay; Tory, Melanie; Carpendale, Sheelagh; Endert, Alex (IEEE Computer Graphics and Applications, 2019)
Promoting a wider range of contribution types can facilitate healthy growth of the visualization community, while increasing the intellectual diversity of visualization research papers. In this paper, we discuss the importance of contribution types and summarize contribution types that can be meaningful in visualization research. We also propose several concrete next steps we can and should take to ensure a successful launch of the contribution types.